Surviving male partner violence in Turkey :|women’s stories of powerlessness, empowerment, and recovery - Yalçınöz Uçan, Büşra. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Alternative to the psychopathology-oriented approaches on women’s responses to male partner violence, research grounded on strength-based perspectives has contributed significantly to a better conceptualization of women’s experiences of coping with and surviving violence. Much research in psychology, however, focused on intrapersonal and interpersonal aspects while neglecting the socio-structural determinants of leaving and empowerment. Integrating a feminist, multidimensional approach, the present study provides a contextualized framework of women’s pre- and post-separation processes. As no previous studies in Turkey systematically examined women’s leaving and post separation experiences, this research also aimed to identify the processes shaped by the particular context of the country. The participants included 16 women survivors of male partner violence. Two in-depth interviews were conducted with each woman. The Constructivist Grounded Theory was used for the analysis. The results demonstrated the substantial effect of the degree of women’s socio-economic power on their stay/leave decision-making and their experiences after separation, which indicated the complexity of sociocultural and structural factors in Turkey, incumbering women’s escape and healing. The narratives also revealed nonlinear, coexistent processes that constituted women’s unceasing struggle to survive disempowering circumstances in their lives, both before and after separation. While not reflecting an end to their distress, their efforts to resist violence and powerlessness, as strengthened by the relational and practical support available to them, were shown to evolve into a profound sense of well-being and empowerment. The results are discussed from the perspective of feminist intersectional approaches, and social/clinical implications in relation to the country context are presented.
Keywords: Intimate partner violence -- Turkey.; Intimate partner violence -- Attitudes toward.; Intimate partner violence -- Psychological aspects.